Endogenous money: on banking behaviour in new and post Keynesian models - Co-Pierre Georg; Markus Pasche (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
In New Keynesian as well as in Post Keynesian macroeconomic models, money supply is assumed to be endogenous. The reasons for the endogeneity and the role of the financial sector in the supply process, however, are seen very different. In this paper we explicitly derive the behaviour of the banking sector regarding the supply of loans and the demand for reserves from portfolio and liquidity considerations. As a result, the money multiplier as well as the money base are endogenously determined. Although the microeconomics of the bank behaviour is quite simple, credit and money as well as bonds demand depend on policy variables in a non-linear and non-monotonous way.
Keywords: E51; E44; B22; 330; Endogenous money; loans market; bonds market; central banking; Geldangebot; Bank; Portfolio-Management; Kreditmarkt; Rentenmarkt; Geldpolitik; Ungleichgewichtstheorie; Postkeynesianismus; Theorie